PENGARUH ELABORASI PESAN INFODEMIK VAKSIN COVID-19 TERHADAP PENGAMBILAN KEPUTUSAN VAKSINASI GENERASI Z - Windhiadi Yoga Sembada; Adam Abimanyu; Utih Amartiwi (SOURCE : Jurnal Ilmu Komunikasi, 2023)
This study aims to determine the effect of the elaboration of the Covid-19 vaccine infodemic message on generation Z vaccination decision making using the Elaboration Likelihood theory. The method used in this research is quantitative with the type of explanatory research, which is trying to form a research that explains the correlation between one social phenomenon (variable X) and another social phenomenon (variable Y). Data collection techniques, researchers use survey methods with sampling that has been determined by purposive sampling techniques. The validity test and reliability test stages are used by researchers to test the instruments that have been made. The stages of data analysis that researchers do are correlation coefficient test, simple linear regression test, determination coefficient test and hypothesis testing. The calculation results of the coefficient of determination test show a value of 54.4%, which is the percentage value of the influence caused by the elaboration of the Covid-19 vaccine message on generation Z vaccination decision making, for the remaining percentage value can be effect by other factors that are not the focus of this study. The results of the hypothesis testing in this study state that the elaboration of the Covid-19 vaccine infodemic message has a significant effect on generation Z vaccination decision making.